2020
DOI: 10.1039/d0sc04381h
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative regulation of the mechanical strength of a C–S bond

Abstract: The mechanical strength of individual polymer chains is believed to underlie a number of performance metrics in bulk materials, including adhesion and fracture toughness. Methods by which the intrinsic molecular...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 52 publications
1
3
0
Order By: Relevance
“…For example, the C-S(VI) bond in PSU has rupture force F act[T = 298.15 K, t = 654 s],calc of 1790 pN, which is lower than that of C-S(II) bond in PPS (F act[T = 298.15 K, t = 654 s],calc = 1990 pN). It is consistent to what Craig and co-workers found experimentally 31. It was also found that the C-C bonds in polyethylene (PE) are the most force-resistant among all the polyalkenes.…”
supporting
confidence: 90%
“…For example, the C-S(VI) bond in PSU has rupture force F act[T = 298.15 K, t = 654 s],calc of 1790 pN, which is lower than that of C-S(II) bond in PPS (F act[T = 298.15 K, t = 654 s],calc = 1990 pN). It is consistent to what Craig and co-workers found experimentally 31. It was also found that the C-C bonds in polyethylene (PE) are the most force-resistant among all the polyalkenes.…”
supporting
confidence: 90%
“…gDCC is an extensively studied mechanophore that undergoes ring opening reaction to yield 2,3‐dichloroalkene [32] . Because the rate and extent of mechanophore activation depend on the chain length of the mechanophore‐containing polymers [33] and it is difficult to control molecular weight in polycondensation, we chose gDCC as an internal standard to also be incorporated into polymers as reported in other studies in order to compare the degree of activation for the three regioisomers [10,34–36] . Thus, the ratio of mechanoactivation for cyclobutane relative to gDCC can be used to compare the reactivity difference among the three isomers embedded in polymers with different lengths.…”
Section: Resultsmentioning
confidence: 99%
“…1,2 Since the emergence of the mechanophore concept, 3 chemists have been able to explore and control reactivity under tension with clever molecular designs. 4 Several factors affecting the reactivity under tension have been uncovered such as: the polymer architecture, [5][6][7] the nature of the linker, [8][9][10][11][12] substituents, [13][14][15][16] or dependence on their stereo-, [16][17][18][19][20][21][22] regio-, 18,[23][24][25][26][27] or topochemistry. [28][29][30] These factors usually affect the rate of activation or, more rarely, the outcome of the reaction itself.…”
mentioning
confidence: 99%
“…The reactivity of molecules under tension can significantly deviate from their force-free reactivity. , Since the emergence of the mechanophore concept, chemists have been able to explore and control reactivity under tension with clever molecular designs . Several factors affecting the reactivity under tension have been uncovered such as the polymer architecture, the nature of the linker, substituents, or dependence on their stereo-, regio-, , or topochemistry. These factors usually affect the rate of activation or, more rarely, the outcome of the reaction itself. ,,, The latter case is often the result of a post-transition-state bifurcation on the force-modified potential energy surface (PES). ,, …”
mentioning
confidence: 99%